John Steinbeck in Vietnam. - United States Navy:::Creator::::::::::::
John Steinbeck aboard a river patrol boat, PBR 37, on the Bassac River in southern Vietnam. On the far right is Harold A. Chase (New Bedord, Massachusetts), in the middle is Patrol Officer William A. Lee (Lebanon, Indiana). Original is in the safe.